2012
DOI: 10.1155/2012/593068
|View full text |Cite
|
Sign up to set email alerts
|

Does Personality Predict Depression and Use of an Internet-Based Intervention for Depression among Adolescents?

Abstract: Background. Focus upon depression and prevention of its occurrence among adolescents is increasing. Novel ways of dealing with this serious problem have become available especially by means of internet-based prevention and treatment programs of depression and anxiety. The use of Internet-based intervention programs among adolescents has revealed some difficulties in implementation that need to be further elucidated. The aim of this study is to investigate the association between personality and adolescent depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
13
0
2
Order By: Relevance
“…Firstly, we could distinguish indications for which CCBT is appropriate. In fact, it has been reported that applying CCBT to patients with a personality suitable for it [64] or to those from a technologically-literate generation [19] may contribute to better outcomes. Also, further development of CCBT in terms of sophistication and attractiveness accompanying the rapid progress of information technology [65] might enhance the effectiveness of and adherence to CCBT, such as in the format of a therapeutic computer game [66].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we could distinguish indications for which CCBT is appropriate. In fact, it has been reported that applying CCBT to patients with a personality suitable for it [64] or to those from a technologically-literate generation [19] may contribute to better outcomes. Also, further development of CCBT in terms of sophistication and attractiveness accompanying the rapid progress of information technology [65] might enhance the effectiveness of and adherence to CCBT, such as in the format of a therapeutic computer game [66].…”
Section: Discussionmentioning
confidence: 99%
“…Unguided cCBT allows for privacy, which participants rated as very important [31]. The strongest predictor for use and non-use appeared to be gender, as females are more likely to use unguided cCBT [37]. Guided cCBT was evaluated by participants as useful and 'worth their time' [40].…”
Section: Acceptabilitymentioning
confidence: 99%
“…Table 1 presents details of the included studies (k = 33). Sixteen studies were aimed at computerized treatments, of which nine were unguided computerized treatments (four computer-based and five internet-based) [30][31][32][33][34][35][36][37][38] and seven studies were guided computerized treatments (one computer-based and six internet-bases) [39][40][41][42][43][44][45], two studies at blended treatment [46,47], two studies compared unguided computerized, blended-and face-to-face treatment to no treatment [48,49], and eight studies were aimed at self-help internet-based games [50][51][52][53][54][55][56][57]. Furthermore, two studies that were focused on the use of an online monitoring tool aimed at registering and monitoring treatment progression [58,59] and three studies were aimed at characteristics of online interventions or studied the preferred modes of help seeking [60][61][62].…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emocionalmente, conlleva una anticipación entusiasta y de ansiedad por el futuro, junto con sentimientos de nostalgia o frustración e importantes reajustes psicológicos (Sha-pero et al, 2015). Un período decisivo en el desarrollo de la madurez, donde se construyen los procesos autónomos de adquisición de hábitos que permiten el equilibrio saludable, que prevengan el desarrollo de trastornos clínicos asociados como depresión (Hankin et al, 2015;Guillén, Montaño, Fernández, Gordillo, & Solanes, 2013;Polanczyk, Salum, Sugaya, Caye, & Rohde, 2015;Suetani et al, 2017), trastornos adictivos, ansiedad y estrés o agresividad (Joshi, & Yadav, 2017;Páramo, 2011;Vangberg, 2013) tendencias autodestructivas, entre otros procesos desadaptativos (Gartstein, Slobodskaya, Zylicz, Gosztyla, & Nakagawa, 2010;Lombas, Martín-Albo, Valdivia-Salas, & Jiménez, 2014;López-Soler, Alcántara, Fernández, Castro, & López-Pina, 2010). Cloninger (2003), propone en su Modelo Psicobiológico de Personalidad la existencia de "causas internas que subyacen al comportamiento individual y a la experiencia de la persona" (Cloninger, 2003, p.3), buscando integrar el substrato biológico de la personalidad con el desarrollo producido por la experiencia y el aprendizaje socio-cultural (García, 2012).…”
unclassified